Percepția populației din valea Dunării românești asupra dezvoltării socioeconomice în perioada postcomunistă. Studiu de caz: sectorul Turnu Măgurele – Giurgiu - Lupu, Laura (Calitatea Vieții, 2018)
In Romania, the transformations during the transition and post-transition period have generated various dynamics in term of socio-economic development. The present paper addresses socio-economic development issues in the Romanian Danube Valley (RDV), Turnu Măgurele – Giurgiu sector, focusing on demographic trends (rural – urban migration, decrease of the number of inhabitants, population aging), public services (health, education, transport) and economic dynamics (agricultural decline, deindustrialization, unemployment, poverty) over the last 27 years in the studied area. Based on data exploration techniques of related indicators and indices (e.g. unemployment rate, net migration rate, aging index, poverty rate, Gini coefficient), the study describes the main influencing factors of quality of life. In the analyzed sector of the Romanian Danube Valley socioeconomic development is investigated through a perception study at household level based on 204 questionnaires. The outcomes reveal the socio-economic decline of the area (poverty, lower living standards, rural–urban inequalities, disparities in the access to health services, increasing unemployment, migration, etc.) and the vulnerability of the social groups. The study found that more cooperation and attention from the local authorities and stakeholders is needed to ensure quality of life. The response measures to socio-economic inequalities in the sector and RDV are discussed in a view of the existing development strategies, either at local, regional or national level.